胸腔镜辅助小切口治疗多形性肺癌28例疗效观察 (Zhongguo Fei Ai Za Zhi, 2010)
BACKGROUND AND OBJECTIVE: Video-assisted mini-thoracoscopy (VAMT) has been used for pulmonary lobectomy for 20 years, which has many merits including small wound, less pain and quick recovery. VAMT is the tendency of pectoral minimally invasive surgical treatment. The aim of this study is to evaluate the efficacy of video-assisted mini-thoracoscopy (VAMT) for radical resection of pleomorphic carcinoma of the lung. METHODS: Complete resection of pleomorphic carcinoma of the lung was performed on 28 patients by VMAT. A 1.5 cm and a 6 cm to 8 cm incision was made during the operation. Both standard surgical instruments and thoracoscopic set were used to treat the pulmonary vessels, perform lobotomy, and remove the lymph nodes in the mediastinum and pulmonary portal. RESULTS: The operation was completed in all of the cases. No peri-operative death occurred. The total volume of hemorrhage was 200 mL to 450 mL (mean, 300 mL). The patients received chest drainage for 3 to 8 days after the operation (mean, 5 d). The time in hospital was 7 d-14 d (mean, 12 d). Five-year overall survival and disease-free survival were 39.2% and 47.1%, respectively. Follow-up was available in all 28 patients for up to 2 to 91 months. Among the 28 cases, only 2 patients died 2 months after the operation, the rest all live up over 1 year. 3-year survival rate was 60.7% (95%CI: 40.3%-81.1%). CONCLUSION: VAMT is effective for radical resection of pleomorphic carcinoma of the lung in a short term. Combination the superiority of traditional procedure and VATS, so VAMT is safe and reliable for radical resection of pleomorphic carcinoma of the lung.